ANALYSIS OF ENGLISH LANGUAGE STUDENTS’ DIFFICULTIES IN LEARNING GRAMMAR AT MUHAMMADIYAH UNIVERSITY OF MATARAM - Mufida Mufida; Ilham Ilham; Edi Edi; Irwandi Irwandi (Wiralodra English Journal, 2025)
This study investigates the factors affecting grammar mastery among English language students at Universitas Muhammadiyah Mataram using a descriptive qualitative approach. It involves 25 first-semester students who participated in grammar tests, with data analysed through the Miles and Huberman model: data reduction, data display, and conclusion drawing. The findings highlight several significant challenges. First, the dominance of theoretical teaching methods without adequate practical application makes grammar learning difficult for students. Students often memorize rules but struggle to apply them in real contexts. Second, the lack of opportunities to practice speaking English limits students’ ability to internalize grammatical structures, reducing their confidence and fluency. Although English exposure through media is frequent, it is generally passive such as listening to songs or watching movies without interactive engagement. Third, students face challenges in understanding English vocabulary, particularly idiomatic expressions and cultural references, which are often absent from local linguistic environments. These unfamiliar elements create confusion and hinder comprehension. The study suggests that grammar instruction should be more communicative, include cultural integration, and provide active learning opportunities to enhance grammar mastery. These findings offer valuable insights for improving English grammar teaching strategies in similar EFL contexts.